EU employment and social situation quarterly review - September 2013. Special edition: annual overview (Luxembourg, 2013)
"There are signs of fragile economic recovery, but economic growth is unlikely to be sustained unless it is inclusive and job rich, especially while labour market and social conditions remain extremely challenging and divergence between countries is growing. The EU is struggling with many challenges such as high unemployment, low employment, and labour mismatches, and increasing numbers of young people not in education, employment and training. Poverty and social exclusion has increased, following rise in jobless households and rise in in-work poverty, and household incomes declined. Divergences between countries have been growing, especially within the Euro Area. The South and periphery of the EU have been particularly hard hit. But also more resilient Member States get affected by spill-overs through reduced aggregate demand, eroded confidence, and contagion via the financial markets. These might threaten core objectives of the EMU: to benefit all its members by promoting economic convergence and to improve the lives of citizens in the Member States. "